دراسة النشاط الجهازي للمبيد الفطري كربندازيم في نباتات الخيار وتأثيره في نمو النباتات - طويل, محمد; القبيلي, ميس (Latakia University Journal -Biological Sciences Series, 2016)
درسنا في هذا البحث النشاط الجهازي للمبيد الفطري كربندازيم في نباتات الخيار صنف ملتون (F1 هجين)، تمَّ ذلك من خلال المعاملة بالمبيد عن طريق التربة وفق التراكيز 0.25 – 0.5- 1.0-2.5 غ مادة فعالة لكل كغ تربة، والرش الورقي للنباتات بعمر شهر (ثلاث أوراق حقيقية) وفق التركيز المنصوح به وهو 0.25 غ مادة فعالة لكل لتر ماء ونصف التركيز وضعفه. اعتمدت الطريقة الحيوية للكشف عن النشاط الجهازي للمبيد، وذلك بوضع الأجزاء النباتية بتماس مباشر مع أبواغ فطر حساس للمبيد المطلوب الكشف عنه على بيئة PDA ضمن أطباق بتري.تم الكشف عن وجود الكربندازيم في الجذر والأوراق الفلقية والورقة الحقيقية الأولى بعد 20 يوماً من معاملة التربة وذلك لجميع التراكيز، كما تم ملاحظة مثابرة المبيد في النباتات بعد أربعين يوماً. أما في معاملة الرش الورقي فتمّ الكشف عن المبيد في جميع التراكيز بعد يوم من الرش، وللتركيز المنصوح به وضعفه فقط بعد خمسة وعشرة وعشرين يوماً من الرش.We studied in this research the systemic activity of fungicide carbendazim in cucumber plants (Hybrid F1 Milton). The soil was treated with fungicide with concentrations of 0.25 - 0.5 - 1.0 - 2.5 g active ingredient per kg of soil and the month-old plants was sprayed (three true leaves) with the recommended concentration 0.25 active ingredient per liter of water, half and double of concentration. Bioassay method was used to detection the systemic activity of fungicide by putting the plant parts in direct contact with sensitive fungus spores within petri dishes that containing PDA.It has been detected the presence of carbendazim in the root , cotyledonary leaves and first real leaf after 20 days from treatment the soil for all concentrations, as it was observed the fungicide persistence in plants after forty days. In the spraying treatment, It has been detected the presence of carbendazim after one day for all concentrations and for the recommended and double concentration only after five, ten and twenty days of spraying.